Challenges in testing genetically modified crops for potential increases in endogenous allergen expression for safety. Issue 2 (4th December 2012) - Panda, R.; Ariyarathna, H.; Amnuaycheewa, P.; Tetteh, A.; Pramod, S. N.; Taylor, S. L.; Ballmer‐Weber, B. K.; Goodman, R. E.
Abstract Premarket, genetically modified (GM) plants are assessed for potential risks of food allergy. The major risk would be transfer of a gene encoding an allergen or protein nearly identical to an allergen into a different food source, which can be assessed by specific serum testing. The potential that a newly expressed protein might become an allergen is evaluated based on resistance to digestion in pepsin and abundance in food fractions. If the modified plant is a common allergenic source (e.g. soybean), regulatory guidelines suggest testing for increases in the expression of endogenous allergens. Some regulators request evaluating endogenous allergens for rarely allergenic plants (e.g. maize and rice). Since allergic individuals must avoid foods containing their allergen (e.g. peanut, soybean, maize, or rice), the relevance of the tests is unclear. Furthermore, no acceptance criteria are established and little is known about the natural variation in allergen concentrations in these crops. Our results demonstrate a 15‐fold difference in the major maize allergen, lipid transfer protein between nine varieties, and complex variation in IgE binding to various soybean varieties. We question the value of evaluating endogenous allergens in GM plants unless the intent of the modification was production of a hypoallergenic crop.